Expansion of the clinical phenotype of the distal 10q26.3 deletion syndrome to include ataxia and hyperemia of the hands and feet. Issue 6 (21st April 2017) - Lacaria, Melanie; Srour, Myriam; Michaud, Jacques L.; Doja, Asif; Miller, Elka; Schwartzentruber, Jeremy; Goldsmith, Claire; Majewski, Jacek; ,; Boycott, Kym M.
Abstract : Distal deletion of the long arm of chromosome 10 is associated with a dysmorphic craniofacial appearance, microcephaly, behavioral issues, developmental delay, intellectual disability, and ocular, urogenital, and limb abnormalities. Herein, we present clinical, molecular, and cytogenetic investigations of four patients, including two siblings, with nearly identical terminal deletions of 10q26.3, all of whom have an atypical presentation of this syndrome. Their prominent features include ataxia, mild‐to‐moderate intellectual disability, and hyperemia of the hands and feet, and they do not display many of the other features commonly associated with deletions of this region. These results point to a novel gene locus associated with ataxia and highlight the variability of the clinical presentation of patients with deletions of this region.